TELAAH TAFSIR SUFISTIK: Studi Atas Penafsiran Ayat-Ayat Tentang Nur dalam Tafsir Al-Qur’an Al-‘Azhim Karya Sahal Al-Tustari - Baihaki Baihaki; Nor Faridatunnisa (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2021)
This article describes the interpretation of nur verses according to Sahal bin Abdullah al-Tustari in his tafsir book entitled Tafsir al-Qur'an al-'Azhim. Nur which means light according to the Sufis' view has an important position in the enlightenment of the human soul, without the nur given by Allah, it is difficult for humans to reveal the inner meaning of a verse, as they believe that the meaning of zahir is an usual meaning that can be read. through he said. Meanwhile, the inner meaning is the meaning that is specifically desired. Interpreting the Koran in this model is not enough to range in language alone, but there is nur aspects given by Allah in the heart of a person who is clean in spirit and mind. Therefore, the nur theme among the Sufis has a central position for the enlightenment of the human soul in guiding and finding true happiness and truth. The method used in this research is descriptive-analytic with the term thematic method, which is a method that collects all the verses concerned with the same theme and then analyzes them one by one. This research found. First, Sahal al-Tustari's interpretation of the verses concerning nur is divided into two parts: first, the interpretation of the verses which directly contains the editorial of al-nur. Second, the interpretation of nur in verses that do not contain the al-nur. Which has two kinds of interpretation, namely exoteric and esoteric. As a result, there are eight meanings of nur described by Sahal al-Tustari in his tafsir book and the theory about nur Muhammad is the most distinctive meaning striking in his esoteric interpretation, even this can be traced through the tafsir book afterward.